A study of the interplay effect for VMAT SBRT using a four‐axes motion phantom. Issue 8 (23rd June 2020) - Leste, Jermey; Medjahed, Imene; Arnaud, François‐Xavier; Ferrand, Regis; Franceries, Xavier; Bardies, Manuel; Simon, Luc
Abstract: Purpose: To assess the accuracy of volumetric modulated arc therapy (VMAT) stereotactic body radiation therapy (SBRT) when treating moving targets (such as lung or liver lesions), focusing on the impact of the interplay effect in the event of complex breathing motion and when a gating window is used. Methods: A dedicated programmable motion platform was implemented. This platform can carry large quality assurance (QA) phantoms and achieve complex three‐dimensional (3D) motion. Volumetric modulated arc therapy SBRT plans were delivered with TrueBeam linac to this moving setup and the measured dose was compared to the computed one. Several parameters were assessed such as breathing period, dose rate, dose prescription, shape of the breathing pattern, the use of a planning target volume (PTV) margin, and the use of a gating window. Results: Loss of dose coverage (D95%) was acceptable in most situations. The doses received by 95% of the CTV, D95% ( C T V m ) ranged from 94 to 101% (mean 98%) and the doses received by 2% of the CTV D2% ( C T V m ) ranged from 94% to 110% of the prescribed dose. A visible interplay effect was observed when no margin was used or when the number of breathing cycles during the treatment delivery was lower than 20. Conclusions: In our clinical context, treating lung and liver lesions using VMAT SBRT is reasonable. The interplay effect was moderated and acceptable in all simulated situations.